Behavioral contrast in one component of a multiple schedule as a function of the reinforcement conditions operating in the following component - Wilton, R. N. (1969)
The key pecks of four pigeons were reinforced on a variable-interval 5-min schedule which operated in each of the four components of a multiple schedule, indicated by red, green, yellow, and blue stimuli and presented in such an order that the red stimulus always preceded the yellow and the green stimulus always preceded the blue. After establishing baseline rates, the reinforcement schedule associated with the blue and yellow components was altered so that one was now an extinction schedule and the other was a variable-interval 1-min schedule. In a second experimental stage, the blue stimulus was interchanged with the yellow so that the red stimulus preceded the blue and the green stimulus preceded the yellow. In both experimental stages the response rate in the variable-interval 5-min component that preceded the extinction component was higher than the response rate in the variable-interval 5-min component that preceded the variable-interval 1-min component. The results were discussed in relation to the importance of stimulus ordering in experiments concerned with investigating behavioral contrast.